Until it fades : a novel - Tucker, K. A. (Kathleen A.), 1978- (Atria Paperback, 2017)
"A sexy new romance about a small-town woman who saves the life of a mysterious man, and finds herself unexpectedly thrown into a whirlwind love affair, featuring bestselling author K. A. Tucker's signature "well-constructed, pulse-pounding suspense" (USA TODAY). Twenty-four-year-old truck stop waitress and single mother Catherine Wright has simple goals: to give her five-year-old daughter a happy life and to never again be the talk of the town in Balsam, Pennsylvania: population two thousand outside of tourist season. And then one foggy night, on a lonely road back from another failed attempt at a relationship, Catherine saves a man's life. It isn't until after the police have arrived that Catherine realizes exactly who it is she has saved: Brett Madden, hockey icon and media darling. Catherine has already had her fifteen minutes of fame and the last thing she wants is to have her past dragged back into the spotlight, only this time on a national stage. So she hides her identity. It works. For a time. But when she finds the man she saved standing on her doorstep, desperate to thank her, all that changes. What begins as an immediate friendship quickly turns into something neither of them expected. Something that Catherine isn't sure she can handle; something that Catherine is afraid to trust. Because how long can an extraordinary man like Brett be interested in an ordinary woman like Catherine...before the spark fades?"--